2011
DOI: 10.1007/978-3-642-19263-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network for Assessment of Grain Losses for Paddy Combine Harvester a Novel Approach

Abstract: Abstract. Paddy is a staple food for more than 93 countries and it will stay of life for future generations. Harvesting is one of the vital operations in crop production and timely harvesting is essential for getting maximum yield. Moisture content and forward speed are the two factors to overcome the post harvest losses and minimise the quantitative losses. In this paper, an artificial neural network is introduced to assess the grain losses in the field condition. The simulation result shows that the ANN meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Four pressure sensors were mounted on the cleaning section to monitor the sieve load [11][12][13] . An artificial neural network was introduced to assess the grain losses in the field condition and the simulation result showed that the ANN method was appropriate and feasible to assess the grain losses [14] .…”
Section: Introduction mentioning
confidence: 99%
“…Four pressure sensors were mounted on the cleaning section to monitor the sieve load [11][12][13] . An artificial neural network was introduced to assess the grain losses in the field condition and the simulation result showed that the ANN method was appropriate and feasible to assess the grain losses [14] .…”
Section: Introduction mentioning
confidence: 99%
“…Some scientific research institutes and universities, both local and abroad, have performed research on the biomechanical properties of maize and ear picking related injury (Martin et al 1987;Hiregoudar et al 2011;Cook et al 2014;Saini et al 2015;Cheng et al 2016;Yang et al 2016;Aguayo et al 2017;Fu et al 2019Fu et al , 2020. Balastreire et al (1982) accurately measured the critical value of the fracture toughness of maize.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the cleaning efficiency of high impurity content, Craessaerts et al, (2010) developed a fuzzy control strategy by installing wind speed sensors and pressure sensors on the cleaning sieve, which could improve the detection and prediction of the cleaning loss status [9]. At the same time, Hiregoudar et al, (2011) developed a grain detection model for high impurity content cleaning process by artificial intelligence and neural networks [10]. The fuzzy logic control model for the combine harvester's cleaning system was a mature method and technique that can predict and control the cleaning loss rate [11].…”
Section: Introductionmentioning
confidence: 99%